Receptor-mediated leukaemogenesis: hypothesis revisited. - Neil, J. C. (Nature Publishing Group, 1988)
The discovery of the first example of retroviral transduction of an immunological effector molecule has led us to reconsider the possible importance of cell surface receptors of the immune system in leukaemia development. Antigen receptors on lymphoid cells not only bind external ligands but are crucial in the control of cellular proliferation. The concept of autocrine stimulation in oncogenesis is already well established and we see no reason to exclude the possibility of analogous mechanism operating through antigen receptors. At present, we are investigating the oncogenic function of the retrovirus (FeLV-T17) carrying a T-cell receptor gene (v-tcr). In addressing the general concept of oncogenesis by ligand/receptor interactions in the immune system we face the problem of the diversity and, for T-cell antigen receptors, the complex nature of receptor-ligand interaction. Nevertheless, the implications of the model encourage us to continue to search for new experimental tools and approaches to the question.